2018
DOI: 10.1002/jbmr.3419
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Functional Variants at 13q14 Risk Locus for Osteoporosis Regulate RANKL Expression Through Long-Range Super-Enhancer

Abstract: RANKL is a key regulator involved in bone metabolism, and a drug target for osteoporosis. The clinical diagnosis and assessment of osteoporosis are mainly based on bone mineral density (BMD). Previous powerful genomewide association studies (GWASs) have identified multiple intergenic single-nucleotide polymorphisms (SNPs) located over 100 kb upstream of RANKL and 65 kb downstream of AKAP11 at 13q14.11 for osteoporosis. Whether these SNPs exert their roles on osteoporosis through RANKL is unknown. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 68 publications
(145 reference statements)
1
27
0
Order By: Relevance
“…Recent studies shown that noncoding GWAS SNPs regulate distal target genes via long‐range looping formation. ( 8,23,41,42 ) Similarly, we first demonstrated that NEAT1 could be regulated by one distal noncoding SNP (rs12789028) associated with eBMD through long‐range chromatin interaction (113 kb) in an allele‐specific manner. In consistent with the GWAS association analyses, our functional assays showed that the reported osteoporosis risk allele of rs12789028‐G augments NEAT1 expression compared with rs12789028‐A, whose increased expression further decreases bone mass by promoting osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies shown that noncoding GWAS SNPs regulate distal target genes via long‐range looping formation. ( 8,23,41,42 ) Similarly, we first demonstrated that NEAT1 could be regulated by one distal noncoding SNP (rs12789028) associated with eBMD through long‐range chromatin interaction (113 kb) in an allele‐specific manner. In consistent with the GWAS association analyses, our functional assays showed that the reported osteoporosis risk allele of rs12789028‐G augments NEAT1 expression compared with rs12789028‐A, whose increased expression further decreases bone mass by promoting osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 95%
“…It is possible that base pair change at these SNPs may affect the binding of the transcription factor, resulting in the regulation of RANKL expression. This particularly applies to rs9533090, where deletion of the region harboring this SNP could result in the reduction of RANKL expression (34). The SNP rs9533090 can be C or T; however, allele C has greater ability to recruit the transcription factor nuclear factor I C compared with allele T, and may thus more efficiently elevate enhancer activity and increase RANKL expression (33); therefore, it is plausible to consider an association between rs9533090 and osteoporosis.…”
Section: Haplotype Frequency ----------------------------------------mentioning
confidence: 99%
“…Diseases-related cells acquire SEs through various mechanisms, including (i)mutations and genomic alterations like deletions, duplications, translocations, insertions, inversions (Mansour et al, 2014;Oldridge et al, 2015;Zhang et al, 2019); (ii) single-nucleotide polymorphisms (SNPs) (Zhu et al, 2018); (iii) chromosomal rearrangements (Affer et al, 2014;Gröschel et al, 2014;Demchenko et al, 2016); and (iv) 3D genome structural changes (Furlong and Levine, 2018). Once the SEs originated through the above mechanisms, resulting in the dysregulation of nearby SEs-target genes, which ultimately accelerates the deterioration of diseases.…”
Section: The Identification Of Sesmentioning
confidence: 99%
“…Osteoporosis has become a global health concern. Zhu et al (2018) found a SE-associated gene-RANKL-was critical for the progress of osteoporosis, by analyzing the ChIPseq Data from ENCODE. Some significant genome-wide association studies (GWAS) have shown that single nucleotide polymorphisms (SNPs) near RANKL are associated with osteoporosis on chromosome 13q14.11 (Zhang et al, 2014;Kuosmanen et al, 2016).…”
Section: Ses In Osteoporosismentioning
confidence: 99%
See 1 more Smart Citation